A giant leap for commercial space travel. - Oberg, J.
The 21st of June 2004 marked the launch of SpaceShipOne, a privately funded space plane designed for commercial space travel, at the Mojave Airport in California. SpaceShipOne was designed by Burt Rutan and his team at Scaled Composites LLC and was funded by Paul Allen, co-founder of Microsoft Corp. This marked the 14th piloted flight of the plane's test program, the highest and at more than 4,000 km/h, the fastest. Designing an aerospace craft to operate across a vast range of air speed with major changes in center of mass as the fuel burns was a daunting challenge that Rutan's team overcame by actually hinging the aft fuselage. The twin tails swing upward once the rocket burn is complete, so that when the craft falls back into the atmosphere, the trailing tails keep the craft's bottom facing into the wind. Once the air speed drops enough, the tails swing back down into their normal glide position. While some anomalies cropped up during the test flight, there is no doubt in the mind of the design team that can overcome these with a healthy mix of intuition and inspiration.
Keywords: SpaceShipOne; Aerospace craft; Carefree reentry design; Commercial space travel; Space tourism; Zero gravity